Changing the face of engineering the African American experience - Slaughter, John B.; Tao, Yu; Pearson, Willie Jr. 1945- (Johns Hopkins University Press, 2015)
"For much of America's history, African Americans were discouraged or aggressively prevented from becoming scientists and engineers. Those who did enter STEM fields found that their inventions and discoveries were often neither recognized nor valued. Even today, particularly in the field of engineering, the participation of African American men and women is shockingly low, and some evidence indicates that the situation might be getting worse. In Changing the Face of Engineering, twenty-four eminent scholars address the underrepresentation of African Americans in engineering from a wide variety of disciplinary and professional perspectives while proposing workable classroom solutions and public policy initiatives. They combine robust statistical analyses with personal narratives of African American engineers and STEM instructors who, by taking evidenced-based approaches, have found success in graduating African American engineers. Changing the Face of Engineering argues that the continued underrepresentation of African Americans in engineering impairs the ability of the United States to compete successfully in the global marketplace. This volume will be of interest to STEM scholars and students, as well as policymakers, corporations, and higher education institutions"..
Includes bibliographical references and index
Keywords: EDUCATION / Higher; SOCIAL SCIENCE / Black Studies (Global); TECHNOLOGY & ENGINEERING / General; Ingenieurwissenschaften; Schwarze. USA; African American engineers; Engineering -- Study and teaching (Higher) -- United States; African Americans -- Education (Higher); USA